INCREASING LEARNING INTEREST AND LEARNING OUTCOMES OF AUTOMOTIVE BASIC WORK BY APPLYING PROJECT-BASED LEARNING MODEL - Dimas Ilham Budiman; Nurcholish Arifin Handoyono; Rabiman Rabiman (Universitas Sultan Ageng Tirtayasa, 2020)
The research aims to increase the learning interest and learning outcomes of automotive basic work. This type of research is classroom action research with three cycles, each cycle consisting of four stages, namely planning; action, observation, reflection. The research subjects were students of class X TSM SMK Tunas Bangsa Wanareja with a total of 19 students. The object of research is the learning interest and learning outcomes of Automotive Basic Work. Data analysis techniques using quantitative analysis. The results showed that the application of the PjBL model could increase the learning interest and learning outcomes of Automotive Basic Work. Increased learning interest can be seen from the results of the first cycle of 55.53%, increased in the second cycle to 66.38% and increased again in the third cycle to 80.59%. Increased learning outcomes can be seen from the results of the first cycle of 52.63% increased in the second cycle to 68.42% and increased again in the third cycle to 89.47%.